Analysis of lymph node recurrence patterns and risk factors in locally advanced esophageal carcinoma following neoadjuvant therapy - Liu, Yingxin; Wang, Xiaojun; Ni, Zixuan; Zeng, Qiang; Li, Yutao; Zhang, Puchang; Qian, Pudong; Liu, Yatian (Frontiers in Oncology, 2025)
BackgroundAlthough neoadjuvant therapy followed by surgery is the standard treatment for resectable locally advanced esophageal carcinoma, heterogeneity exists in neoadjuvant regimens within real-world practice. This study characterizes lymph node recurrence (LNR) patterns and compares LNR risk factors across different neoadjuvant approaches to better elucidate therapeutic efficacy.MethodsData were collected from esophageal carcinoma (EC) patients who underwent surgery following neoadjuvant therapy between January 2018 and December 2023. Neoadjuvant regimens included neoadjuvant chemotherapy (NCT), neoadjuvant chemoimmunotherapy (NICT), and neoadjuvant chemoradiotherapy (NCRT)/neoadjuvant chemoradiotherapy combined with immunotherapy (NCRT/NICRT). Regional lymph node stations were defined per the Japanese Esophageal Society (JES) criteria. Cox proportional hazards models were used to identify factors associated with LNR.ResultsThis study enrolled 658 patients, including 195 with postoperative LNR. Among all EC cases, the most frequent recurrence sites were No. 106tb (5.5%), No. 109 (5.5%), and No. 104 (8.7%). The most frequent recurrence sites in the NCT group were No. 104 (10.0%) and No. 106tb (7.9%); in the NICT group, No. 104 (8.2%) was the most common; in the NCRT/NICRT group, No. 101 (7.0%) and No. 104 (7.0%) demonstrated the highest recurrence rates. In upper thoracic EC, No. 101, No. 104, and No. 105 were common recurrence sites with metastasis rates exceeding 5%; in mid-thoracic EC, No. 104 (11.9%) showed the highest recurrence frequency; in lower thoracic and gastroesophageal junction EC, No. 104 (5.5%) and No. 16 (4.8%) were frequent recurrence locations. Lymph node dissection count and ypT and/or ypN stage correlated with recurrence risk across neoadjuvant regimens. Adjuvant radiotherapy demonstrated lower lymph node metastasis rates in the tracheoesophageal groove and upper mediastinal LNR.ConclusionsThe tracheoesophageal groove and supraclavicular lymph nodes represent common recurrence sites in neoadjuvant therapy and upper thoracic EC. Lower thoracic and gastroesophageal junction EC require vigilance for the risk of supraclavicular nodal metastasis. Lymph node yield and T/N stages correlate with recurrence risk.